Epidermal growth factor receptor-dependent maintenance of cardiac contractility. Issue 5 (23rd April 2021) - Guo, Shuchi; Okyere, Ama Dedo; McEachern, Erin; Strong, Joshua L; Carter, Rhonda L; Patwa, Viren C; Thomas, Toby P; Landy, Melissa; Song, Jianliang; Lucchese, Ana Maria; Martin, Thomas G; Gao, Erhe; et al.
Abstract: Aims: Epidermal growth factor receptor (EGFR) is essential to the development of multiple tissues and organs and is a target of cancer therapeutics. Due to the embryonic lethality of global EGFR deletion and conflicting reports of cardiac-overexpressed EGFR mutants, its specific impact on the adult heart, normally or in response to chronic stress, has not been established. Using complimentary genetic strategies to modulate cardiomyocyte-specific EGFR expression, we aim to define its role in the regulation of cardiac function and remodelling. Methods and results: A floxed EGFR mouse model with α-myosin heavy chain-Cre-mediated cardiomyocyte-specific EGFR downregulation (CM-EGFR-KD mice) developed contractile dysfunction by 9 weeks of age, marked by impaired diastolic relaxation, as monitored via echocardiographic, haemodynamic, and isolated cardiomyocyte contractility analyses. This contractile defect was maintained over time without overt cardiac remodelling until 10 months of age, after which the mice ultimately developed severe heart failure and reduced lifespan. Acute downregulation of EGFR in adult floxed EGFR mice with adeno-associated virus 9 (AAV9)-encoded Cre with a cardiac troponin T promoter (AAV9-cTnT-Cre) recapitulated the CM-EGFR-KD phenotype, while AAV9-cTnT-EGFR treatment of adult CM-EGFR-KD mice rescued the phenotype. Notably, chronic administration of the β-adrenergic receptor agonist isoproterenol effectively and reversibly compensated for the contractile dysfunction in the absence of cardiomyocyte hypertrophy in CM-EGFR-KD mice. Mechanistically, EGFR downregulation reduced the expression of protein phosphatase 2A regulatory subunit Ppp2r3a/PR72, which was associated with decreased phosphorylation of phospholamban and Ca 2+ clearance, and whose re-expression via AAV9-cTnT-PR72 rescued the CM-EGFR-KD phenotype. Conclusions: Altogether, our study highlights a previously unrecognized role for EGFR in maintaining contractile homeostasis under physiologic conditions in the adult heart via regulation of PR72 expression. Graphical Abstract: